2020
DOI: 10.1016/j.jocn.2020.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal deterioration of visual and auditory hallucinations in schizophrenia presents V-shaped cognition impairment and widespread reduction in brain gray matter-A pilot study

Abstract: Schizophrenic patients often experience visual hallucinations (VHs) and auditory hallucinations (AHs); however, brain aberrations associated with combined VH and AH in schizophrenic patients remains poorly documented. Changes to the brain and cognition during the first episode of untreated schizophrenic patients (FUSCH) with both VHs and AHs (FUSCHVA) were evaluated. One-hundred and fifty-seven patients were enrolled that had FUSCH (1) with VHs but not AHs (FUSCHV), and (2) with AHs but not VHs (FUSCHA), plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…We also observe that facial expressivity was decreased as subjects endorsed greater positive symptoms of hallucinations, delusions, and paranoid ideation. This finding is consistent with evidence that social and cognitive impairment, which falls into the negative symptom cluster, mechanistically relates to neurodegeneration that also impacts visual and auditory hallucinations (Bersani et al, 2013;Jenkins et al, 2018;Zhuo et al, 2020).…”
Section: -Discussionsupporting
confidence: 89%
“…We also observe that facial expressivity was decreased as subjects endorsed greater positive symptoms of hallucinations, delusions, and paranoid ideation. This finding is consistent with evidence that social and cognitive impairment, which falls into the negative symptom cluster, mechanistically relates to neurodegeneration that also impacts visual and auditory hallucinations (Bersani et al, 2013;Jenkins et al, 2018;Zhuo et al, 2020).…”
Section: -Discussionsupporting
confidence: 89%
“…For instance, schizophrenia patients with AVH showed increased ALFF in the bilateral temporal role and parahippocampus gyrus, while decreased ALFF in the parietal, occipital, and cingulate cortex. In the structural domain, smaller gray matter volume (GMV) with AVH in schizophrenia patients, as measured with voxel-based morphometry (VBM), have been identified in a wide range of brain regions, including the prefrontal, parietal, temporal, and occipital cortex ( Dean et al, 2020 ; Zhuo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that patients with schizophrenia showed signi cantly higher theta power in the SG paradigm than healthy controls, similar to the conclusions mentioned in the literature [5] In many patients with schizophrenia, various evoked potential patterns in vitro and in vivo suggested that stimuli evoked early theta frequency oscillations. Previous studies have reported dysfunction in the left temporal region involved in speech classi cation in schizophrenia and reduced gray matter volume in the occipital, parietal, frontal, and temporal cortex in schizophrenia compared with healthy controls [7,15]. Therefore, we analyzed each of the six brain regions, and the results showed that schizophrenic patients showed higher theta oscillations in the whole brain.…”
Section: Abnormal Theta In Schizophrenia In Sg and Mmnmentioning
confidence: 94%
“…Some studies have found that theta activity in both temporal lobes increased in untreated schizophrenic patients [6]. Schizophrenic patients showed dysfunction in the occipital lobe, parietal lobe and temporal lobe cortex in the speech classi cation test [7]. The defect in auditory information processing in schizophrenia was due to the reduction in inhibition caused by the destruction of the inhibition mechanism needed to suppress redundant sound input.…”
Section: Introductionmentioning
confidence: 99%